A revision of the genus Orbilia in the Canary Islands - Quijada, Luis; Baral, Hans-Otto; Beltrán-Tejera, Esperanza (Phytotaxa, 2016)
Based on field work and herbarium studies, a taxonomic revision of the genus Orbilia in the Canary Islands was carried out. Eighteen species of the genus are recognized in the present study. Eight of these are new records for the archipelago (Orbilia cejpii, O. euonymi, O. flavida, O. flavidorosella, O. hesperidea, O. scolecospora, O. vinosa and O. vitalbae). Three of them are here described in detail (O. cejpii, O. flavida and O. vitalbae), because they were not reported again since their first publication. Corrections and clarifications about the identity of four previously reported species (O. alnea, O. auricolor, O. delicatula and O. epipora) are provided, being renamed to O. eucalypti, O. tenuissima, O. xanthostigma, and O. dryadum, respectively, the last one being a new combination for O. alnea var. dryadum. Two species with a rather short original diagnoses reported for the Canary Islands are redescribed in detail (O. corculispora and O. gambelii), and those being endemic for the archipelago are illustrated and briefly discussed (Orbilia adenocarpi, O. asomatica, O. pisciformis and O. succulenticola). A key for the identification of these species, a discussion about closely related taxa, notes on their global distribution, and ecological data are provided.